Evaluation Of Suitability Of Permitted Delay Detonators Vis-avis Their Delay Timing For Use In Underground Coal Mines - Harsh Kumar Verma (International Society of Explosives Engineers, 2008)
Blasting off-the-solid is the most commonly used method during development of galleries in Bord and Pillar method of underground coal mining. In this method, only P5 explosives are used with permitted delay detonators in accordance with the safety requirements stipulated by the regulatory bodies. Delay detonators made with pyrotechnic delay compositions have inherent scattering in their delay timings. It is desirable to use precise detonators to achieve better fragmentation, less vibration and noise. Overlapping of delay period is undesirable from production as well as safety point of view.